Predictable Models and Experimental Measurements for Electric Properties of Polypropylene Nanocomposite Films - Ahmed Thabet; Youssef A. Mobarak (Institute of Advanced Engineering and Science, 2016)
This paper processed and characterized cost-fewer polypropylene (PP) nanocomposite films; an experimental work has been investigated for studying the electric properties of the new nanocomposite materials and compared with unfilled industrial materials in a frequency range up to 1 kHz. A small addition of nanoparticles (clay, and fumed silica) to polypropylene showed appreciable improvement in the electric reactance and conductance at different frequency up to 1kHz, in addition, an electric spectroscopy has been measured the electric properties of polypropylene with and without nanoparticles under variant temperatures (20°C, and 60°C). Cambridge Engineering Selector (CES) program were carried out the electrical/mechanical predictable models for the suggested materials. Finally, this paper leads to synthesize electrical insulating polypropylene nanocomposite films where the electrical properties are properly maintained in order to achieve more cost-effective, energy-effective and hence environmentally better materials for the electrical insulation technology.